Experiment study of using parallel plate sensor for the detection of conductive material - N. Lokmanulhakim; W .N. Abd Rashid; N. H. Hussin; M. F. Mukhtar (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Gold is the yellow precious metal that has been used in many applications likes medicine, electronics, jewelry, investment and others. Thus, gold is one of the commodities which has high demand in the global market. In other to secure the purity of gold and to protect the retailer and consumer from fraud, the detection of gold is very important in the industry. There are many techniques have been used to detect the purity of gold material and those techniques must consider a several factors such as non-destructive, inexpensive, precise, simple and widely accepted by the jewelry industries. Electrical capacitance tomography (ECT) is the most mature non-destructive technique among various tomography. The advantages of ECT are non-radioactive, non-intrusive, high imaging speed and low cost. This paper introduces the ECT using the square sensor. The aim of his paper this to present a new method of verifying the conductive materials using a parallel plate sensor which adopted from the ECT system.